The Effectiveness of Ethno-Religious Based Jigsaw Model to Improve Critical Thinking of PAI in Indonesia - Nursalim, Eko; Satriah, Satriah; Panjaitan, Hendripal; Sari, Windy Dian; Ghofur, Abdul; Sarnoto, Ahmad Zain; Santosa, Tomi Apra (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the irrigators of ethno-religious based jigsaw models to improve students' critical thinking skills in learning Islamic religious education in Indonesia. This type of research is quantitative research with a meta-analysis approach. This study analyzed 27 effect sizes obtained from Google scholars, ERIC, Wiley, and Taylor of Francis from the 2021-2024 issue with 1034 students. The JASP application assists the data analysis in this study.Â Effect size analysis is calculated with a 95% confidence level. The study results concluded that the effect size value obtained through the random effect model was 1,952 (high effect size category). These findings explain that, on average, students who apply the ethno-religious-based jigsaw model are effective in improving students' critical thinking skills in learning Islam. This study provides important information on using the jigsaw model in the future.